Predatory trade finance: The impact of bargaining power and financing constraints on the demand and supply of trade credit - Dmytro Osiichuk; Paweł Mielcarz (Journal of Applied Economics, 2021)
We demonstrate that the "predator-prey" metaphor may be well-suited to describe trade finance mechanisms in emerging economies. Having analyzed the dynamics of trade credit in the Polish corporate sector over the period between 1997 and 2014, we found that suppliers of trade credit were smaller, younger, less liquid, less indebted, and more financially constrained than the beneficiaries thereof. The firms, which increased trade receivables during the analyzed period, improved their asset turnover ratio at the expense of operating profitability. In a quest for growth and cash flows, these firms appear to be forced to supply trade credit to their counterparties with a stronger bargaining position. Companies, which reported higher trade payables, enjoy higher cash flows and a better access to external financing, yet with no improvements to the operating KPIs. In contrast to the conventional wisdom, we hypothesize that trade credit bargaining may be a negative-sum game.
Keywords: 330; emerging economy; Trade credit; working capital